Access to healthcare and self-rated health among refugees in transit and after arrival in Norway. (30th September 2020) - Haj-Younes, J; Strømme, E; Hasha, W; Igland, J; Abildsnes, E; Kumar, B; Diaz, E
Abstract: Background: Lack of basic infrastructure and poor provision of health services in conflict settings and during flight can have a negative impact on health. The overall health status of refugees seems to improve after arrival at a safe destination. This may be related to a safer environment and better access to health care services, but prior studies on this topic are limited. This study aims to assess self-perceived access to healthcare and its relationship with self-rated health (SRH) among refugees in transit and when settled in a host country. Methods: We used data from the CHART study (Changing Health and health care needs Along the Syrian Refugees' Trajectories to Norway), which includes a cohort of 353 Syrian refugees who were contacted in 2017-2018 in Lebanon while waiting for relocation, and one year after their arrival to Norway. Information on self-perceived access to healthcare and its association with SRH was analyzed separately at each time-point. Data analysis was performed with STATA using logistic regression adjusting for age, gender, ethnicity and years of education and presented as adjusted odds ratios (AOR) with 95% CI. Results: Fifteen percent reported good access to healthcare and 62% reported good SRH in Lebanon vs. 91% and 77% respectively, in Norway. Measures in Lebanon showed no association between access to healthcare and good SRH (AOR: 1.2 (0.6-2.2)), and men reported worse access to healthcare than women (AOR: 0.5 (0.3-1.0). In Norway, access to healthcare was strongly associated with good SRH (AOR: 4.7 (2.1-10.7) and was negatively associated with belonging to one specific minority group (AOR: 0.1 (0.0-0.3)). Conclusions: Both SRH and perceived access to care improved from being in transit to being settled in Norway, the latter substantially more. There was a significant association between access to healthcare and good SRH after the refugees' arrival to a safe host country but not in transit. Key messages: Refugee's self-reported health and access to healthcare seem to improve shortly after arrival to a host country. To ensure that the UN'S Sustainable Development Goals concerning health equity are reached, refugees' access to healthcare in transit and its impact on overall health needs to be addressed.